Attachment of immunoglobulin to liposomal membrane via protein carbohydrate - Ming-Ming Chua; Sao-Tah Fan; Karush, Fred (Biochimica et biophysica acta, 1984)
A general method has been developed for the covalent attachment of immunoglobulin molecules to the outer layer of liposomal membranes. Aldehyde groups are generated by the mild oxidation with periodate or galactose oxidase of the carbohydrate groups on the constant region of the heavy chain. The oxidized protein is then reacted with a hydrazide group linked to a membrane component. Detailed studies were carried out with monomers of a monoclonal human IgM and two monoclonal murine IgM antibodies specific for the 1-dimethylaminonaphthalene-5-sulfonyl (Dns) group. Two hydrazide-containing hydrophobic reagents were used: N α -lauroyl, N ϵ -Dns-lysine hydrazide and lauric acid hydrazide. The number of protein aldehyde groups formed was assayed by reaction with N-(2,4-dinitrophenyl)- β-alanylglycylglycine hydrazide. Measurement of the intrinsic affinity for Dns-lysine of the processed anti-Dns IgMs demonstrated no substantial impairment of the specific reactivity of the antibody either from the oxidation step or the subsequent attachment to small unilamellar vesicles. The extent of attachment of antibody to small unilamellar vesicles was evaluated with respect to the mol% of hydrazide in the membrane, the duration of the incubation period for the aldehyde-hydrazide reaction and the ratio of protein to hydrazide. The yield of attached protein was significantly dependent on each of these experimental parameters over the ranges tested. Under the most favorable conditions the extent of covalent attachment of IgMs to small unilamellar vesicles was 535 μg of protein per μ mol of phospholipid, corresponding to 0.3 mol% of protein. Under these conditions, 61% of the total protein was associated with the small unilamellar vesicle fraction after fractionation by gel filtration. The attachment of the antibody to small unilamellar vesicles did not destroy the integrity of the vesicles, as demonstrated by the retention of carboxyfluorescein following initial encapsulation during the formation of small unilamellar vesicles.